Investigation into Safety Profiles of Antiepileptic Drugs and Identification of Predictors for Serious Adverse Events: Insights from National Pharmacovigilance Data - Soo Hyeon Lee; Dae Hyeon Sung; Euna Cho; Jeongah Min; Sooyoung Shin; Yeo Jin Choi (Pharmaceuticals)
Backgrounds/Objectives: This study aims to comprehensively characterize the prevalence and severity of antiepileptic drug (AED)-induced adverse drug events (ADEs) and to identify predictors strongly associated with serious adverse events (SAEs) in both general and geriatric populations. Methods: This cross-sectional study investigated AED-related ADEs reported to the KIDS KAERS DB from January 2014 to December 2023. Disproportionality analysis was performed to detect the association between reported SAEs, and multiple logistic regression was conducted to identify predictors associated with SAEs. Cox’s proportional hazard model was utilized to assess ADE duration in elderly patients aged 60 years and older. Results: More than 50% of 36,809 AED-related ADEs were reported in elderly patients aged 60 years and older, and the prevalence of SAEs was 3.78%. ADEs associated with endocrine disorders had the highest likelihood of SAEs being reported (ROR 15.30), followed by hematological disorders. The predictors associated with elevated SAE risks in the elderly were male sex (OR 1.91; 95% CI 1.62–2.27), aging (OR 1.17; 95% CI 1.04–1.31), and certain AEDs. However, the concomitant administration of acid-suppressive therapy (AST) and opioids was associated with a lower risk of SAEs in the elderly population. Elderly patients not receiving concomitant AST were less likely to experience prolonged ADE duration (HR 0.28, 95% CI 0.07–1.15); however, no substantial differences in ADE duration were observed with the concomitant use of opioids. Conclusions: This study implies significant variability in the frequency, severity, and duration of ADEs depending on the type of AEDs, patient demographics, and concomitant medication use.